Chordoid Meningioma with Extensive Lymphocytic Infiltration Forming Lymphoid Follicles: A Case Report - Suzan Talaat; Farah Farah (Research in Oncology, 2023)
Background: Meningiomas, the most common primary central nervous system (CNS) tumors, include 15 distinct subtypes reflecting its broad morphological spectrum. Most subtypes have a benign clinical course and correspond to CNS World Health Organization (WHO) grade I. Chordoid meningiomas are a rare subtype (0.5% of all meningiomas) with relatively aggressive behavior and are classified as WHO grade II. Case presentation: We present a case of a 20-year-old man who presented to the emergency room with convulsions. A right parietal cerebral mass with peritumoral edema and a significant mass effect was discovered by magnetic resonance imaging. There was no systemic manifestations and hematological tests were normal. He underwent surgery and a histopathological examination of the excised tumor revealed the diagnosis of chordoid meningioma, WHO grade II. In addition, there was dense lymphocytic infiltration forming lymphoid follicles. Conclusion: Chordoid meningioma may be associated with extensive lymphoid infiltration with follicle formation in the absence of systemic or hematologic manifestations.